Immunomodulatory Functions of Mesenchymal Stem Cells in Tissue Engineering - Haojiang Li; Shi Shen; Haitao Fu; Zhenyong Wang; Xu Li; Xiang Sui; Mei Yuan; Shuyun Liu; Guiqin Wang; Quanyi Guo (Hindawi Limited, 2019)
The inflammatory response to chronic injury affects tissue regeneration and has become an important factor influencing the prognosis of patients. In previous stem cell treatments, it was revealed that stem cells not only have the ability for direct differentiation or regeneration in chronic tissue damage but also have a regulatory effect on the immune microenvironment. Stem cells can regulate the immune microenvironment during tissue repair and provide a good "soil" for tissue regeneration. In the current study, the regulation of immune cells by mesenchymal stem cells (MSCs) in the local tissue microenvironment and the tissue damage repair mechanisms are revealed. The application of the concepts of "seed" and "soil" has opened up new research avenues for regenerative medicine. Tissue engineering (TE) technology has been used in multiple tissues and organs using its biomimetic and cellular cell abilities, and scaffolds are now seen as an important part of building seed cell microenvironments. The effect of tissue engineering techniques on stem cell immune regulation is related to the shape and structure of the scaffold, the preinflammatory microenvironment constructed by the implanted scaffold, and the material selection of the scaffold. In the application of scaffold, stem cell technology has important applications in cartilage, bone, heart, and liver and other research fields. In this review, we separately explore the mechanism of MSCs in different tissue and organs through immunoregulation for tissue regeneration and MSC combined with 3D scaffolds to promote MSC immunoregulation to repair damaged tissues.